2020
DOI: 10.1186/s12974-020-1711-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of nerve growth factor (NGF) promotes binding of C/EBPα and contributes to inflammatory hyperalgesia in rats

Abstract: Background: Chronic pain usually accompanied by tissue damage and inflammation. However, the pathogenesis of chronic pain remains unclear. Methods: We investigated the role of nerve growth factor (NGF) in chronic inflammatory pain induced by complete Freund's adjuvant (CFA), explored the methylation status of CpG islands in the promoter region of the NGF gene, and clarified the function and mechanism of C/EBPα-NGF signaling pathway from epigenetic perspective in the chronic inflammatory pain model. Results: CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In the search for new therapeutics, targeting the receptor tyrosine kinase (RTK) family has shown promise for persistent pain conditions ( 6 11 ). Two members of the RTK family are the leukocyte tyrosine kinase (LTK) and the anaplastic lymphoma kinase (ALK), which belong to the insulin receptor family ( 12 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the search for new therapeutics, targeting the receptor tyrosine kinase (RTK) family has shown promise for persistent pain conditions ( 6 11 ). Two members of the RTK family are the leukocyte tyrosine kinase (LTK) and the anaplastic lymphoma kinase (ALK), which belong to the insulin receptor family ( 12 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies showed that the expression of neurotrophic factors is regulated by epigenetic modifications, such as DNA methylation [11,32,33]. DNA methylation plays an important role in a variety of biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our previous work has demonstrated that dysregulation of DNA methylation is involved in the CFA-induced in ammation model [14]. A recent study also described that hypomethylation of nerve growth factors affects In ammatory hyperalgesia in rats [39]. These studies suggested that epigenetic regulation, especially DNA methylation could contribute to in ammatory pain.…”
Section: Introductionmentioning
confidence: 93%